Social Media Performance Study of Open and Distance State University - Gunawan Wiradharma; Rahmat Budiman; Dwi Rahmawati; Kurnia Endah Riana; Meirani Harsasi (Universitas Muhammadiyah Prof. DR. Hamka, 2023)
There are differences in the management of social media at universities that run open and distance higher education systems, such as the Open University. There is an official university account managed by the head office and an official account for unit offices located in the regions. Social media managers must implement effective measures to serve and meet the needs of their stakeholders. The formulation of the problem in this study is how is the performance of social media at the head office and units at the Open University? Socialbakers' professional social media analysis tool is used to monitor social media activity from selected Instagram accounts, namely @univterbuka, @ut_jakarta, @ut.bandung, and @ut.surabaya. This study analyzes the engagement, visual content, copywriting, and content pillars of the account. The results of this study obtain strategies for managing social media at open and distance universities.